Predictive value of the combined use of computed tomography perfusion imaging and blood pressure levels for the prognosis of patients with acute ischemic stroke - Yunxia Qi; Bolin Liu; Yiying Wu; Yifeng Peng (Journal of International Medical Research)
Objective This study aimed to use computed tomography perfusion imaging to investigate the correlation between blood pressure at onset and prognosis in patients with acute ischemic stroke and collateral circulation. It also aimed to verify the value of using blood pressure levels along with computed tomography perfusion imaging for predicting the prognosis of patients with acute ischemic stroke. Methods This retrospective study included 237 patients with acute ischemic stroke. Patients were divided into good prognosis group and poor prognosis group based on the National Institute of Health Stroke Scale scores after clinical discharge. All patients underwent computed tomography perfusion imaging, and image post-processing was performed. Comparison of clinical characteristics, blood pressure levels, and computed tomography perfusion imaging measurements was performed between the two groups. Univariate and multivariate logistic regression analyses and receiver operating characteristic curve analyses were performed for the collected clinical variables. Results Of the 237 recruited patients (aged 67.54 ± 7.75 years; 103 males), 151 had a good prognosis. There were no significant differences in age, systolic blood pressure levels, and alcohol consumption pattern as well as the presence of diabetes, myocardial infarction, coronary atherosclerotic disease, and atrial fibrillation between the good and poor prognosis groups (P > 0.05). There were significant differences in terms of sex distribution and diastolic blood pressure levels between the two groups (P = 0.028 and P < 0.05, respectively). Binary logistic regression analysis revealed that patient prognosis was positively correlated with diastolic blood pressure levels, cerebral blood flow <30%, and mismatch ratio (P < 0.05). Partial correlation analysis revealed a positive correlation between blood pressure levels and cerebral blood flow <30% and mismatch ratio (P < 0.05). Receiver operating characteristic curve analysis revealed that the areas under the blood pressure, cerebral blood flow, mismatch, and combined prognostic value curves were 0.657, 0.683, 0.693, and 0.711, respectively. The sensitivity and specificity were 69.8%, 46.5%, 46.5%, and 57.4% and 60.9%, 90.1%, 95.4%, and 92.1%, respectively. Conclusion There is a correlation between blood pressure levels and prognosis in patients with acute ischemic stroke; however, blood pressure does not affect prognosis by influencing the collateral circulation status in the ischemic area. The combined use of blood pressure levels, cerebral blood flow <30%, and mismatch ratio can improve the prognosis of patients with acute ischemic stroke.